Synthesis and Optical Properties of 1,4- and 1,2-Dicyanodibenzodioxins Possessing Donor–π-Acceptor Architecture - Banerjee, Subhadeep; Chattopadhyay, Anjan; Saini, Praveen; Singh, Keisham Sarjit (Synlett, 2016)
The synthesis and photophysical characterization of isomeric 1,4-and 1,2-dicyanodibenzodioxins is reported. The molecules exhibit optical spectra in the visible region and possess large (ca. 100 nm) Stokes shifts. The synthetic protocol is simple and high-yielding and the presence of replaceable fluorine atoms on the activated dibenzodioxin moiety provides the opportunity for further transformation towards molecules bearing push–pull architecture.
Keywords: dibenzodioxins; push–pull molecules; intramolecular charge transfer; long-wavelength absorption; Stokes shift